2009
DOI: 10.1111/j.1478-3231.2010.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide is related to cardiac function and prognosis in hospitalized patients with decompensated cirrhosis

Abstract: BNP levels in cirrhosis reflect cardiac systolic function and non-cardiac variables that should be considered in their interpretation. BNP is an independent predictor of medium-term survival in advanced cirrhosis, suggesting its utility in risk stratification of decompensated cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 28 publications
3
36
1
1
Order By: Relevance
“…Ascites confers a poor prognosis because of the associated development of spontaneous bacterial peritonitis and hepatorenal syndrome. We found that BNP was an independent predictor in multivariate Cox regression analysis, similar to previous results (Pimenta et al, 2010). BNP concentrations in patients with cirrhosis have been reported to be an independent predictor of medium-term (6-month) survival in hospitalized patients with decompensated cirrhosis, suggesting its utility in risk stratification of patients with advanced cirrhosis (Pimenta et al, 2010); this finder also was supported by the results of Saner et al (2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ascites confers a poor prognosis because of the associated development of spontaneous bacterial peritonitis and hepatorenal syndrome. We found that BNP was an independent predictor in multivariate Cox regression analysis, similar to previous results (Pimenta et al, 2010). BNP concentrations in patients with cirrhosis have been reported to be an independent predictor of medium-term (6-month) survival in hospitalized patients with decompensated cirrhosis, suggesting its utility in risk stratification of patients with advanced cirrhosis (Pimenta et al, 2010); this finder also was supported by the results of Saner et al (2011).…”
Section: Discussionsupporting
confidence: 89%
“…However, high levels of BNP also have been found in congestive states such as heart and renal failure and in chronic liver disease (Passino et al, 2008). Previous studies have shown increased plasma concentrations of BNP in some patients with cirrhosis (Woo et al, 2008;Pimenta et al, 2010), which suggested that cardiac dysfunction might also be present. Recently, several studies have documented that BNP levels were related to the severity of disease in these patients, indicating its predictive value for concomitant cardiac dysfunction and cirrhosis progression (Yildiz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Zwiększone stężenie w surowicy peptydu natriuretycznego typu B jest jednym z nich i dodatkowo stanowi ważny czynnik predykcyjny wyższej śmiertelności [17]. U chorych z marskością wątroby, zwłaszcza w stadium dekompensacji, obserwuje się również zwiększone stężenie w surowicy wysokoczułej troponiny T, które koreluje ze stopniem nasilenia marskości wątroby i jest znacznie wyższe w surowicy chorych w klasie C niż w klasie A. Wydaje się, że znaczenie prognostyczne ma także jeden z markerów stanu zapalnego, czyli rozpuszczalny receptor typu urokinazowego dla aktywatora plazminogenu [15].…”
Section: Biomarkery Użyteczne W Diagnostyce Kardiomiopatii Wątrobowejunclassified
“…The levels of plasma BNP in cirrhosis has been investigated, but its role as prognostic marker of the disease has not been fully explored [27,28]. It is only used as a marker of decompensated cirrhotic cardiomyopathy, indicating the level of cardiac abnormalities, not the level of cirrhosis [21].…”
Section: Role Of Bnp In Cirrhosismentioning
confidence: 99%